2004
DOI: 10.1055/s-2004-823108
|View full text |Cite
|
Sign up to set email alerts
|

Reestablished Circulation After Free Radial Forearm Flap Transfer

Abstract: New circulation in the free flap reestablished at the recipient site is the key to successful microvascular reconstructive surgery. This study is the first evaluation of long-term circulatory changes in nine free radial forearm flap transfers. Postoperatively, color Doppler studies revealed that the flow volume through the arterial pedicle increased rapidly during the first 3 days, gradually increased until day 14 (exceeding flow volume through the facial artery of the unoperated contralateral side), then decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Our results are comparable to data available in literature obtained using other technologies such as laser Doppler 8 and ultrasound Doppler. [4][5][6] For example, intraoperative decreases in blood flow after flap anastomosis 6,8 and postoperative increases/recoveries in blood flow/velocity 4,5,8 were observed, which are similar to our results (see Figs. 6 and 8).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are comparable to data available in literature obtained using other technologies such as laser Doppler 8 and ultrasound Doppler. [4][5][6] For example, intraoperative decreases in blood flow after flap anastomosis 6,8 and postoperative increases/recoveries in blood flow/velocity 4,5,8 were observed, which are similar to our results (see Figs. 6 and 8).…”
Section: Discussionsupporting
confidence: 91%
“…While transcutaneous or implantable ultrasound Doppler technologies are commonly used to assess blood flow through large axial vessels, peripheral flap blood flow remains largely subjective in its clinical assessment. [4][5][6][7] A laser Doppler technique has also been used to monitor blood flow at a tiny spot of superficial tissue, [8][9][10] which may not precisely reflect hemodynamic changes in the bulk flap tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Others have found that the increase in flap pedicle blood velocity and flow is maintained long term, based on measurements obtained months after surgery. 6,22 A potential follow-up to the present study would be to verify that blood velocity differences between flaps with one venous anastomosis and flaps with two venous anastomoses persist, at least during the critical postoperative time period when the risk of thrombosis is greatest.…”
Section: Discussionmentioning
confidence: 95%
“…Ichinose et al 6 previously observed decreased vascular resistance based on blood velocity measurements using color Doppler ultrasonography after free tissue transfer and suggested multiple reasons for this. Sympathetic denervation of the flap should immediately result in vasodilation and decreased vascular resistance throughout the flap.…”
Section: Discussionmentioning
confidence: 98%
“…Hemodynamic changes such as perioperative blood flow and velocity in free tissue transfers have been researched in many ways to improve vascular patency [3][4][5][6][7][8][9][10][11]. Understanding how blood flow is reestablished, maintained, and changed after vascular anastomosis is the most basic element in free tissue transfers.…”
Section: Introductionmentioning
confidence: 99%